Audit Keamanan Sistem Informasi Pada Data Center Menggunakan Standar SNI-ISO 27001 - Syafrinal, S; Agusrijar, A (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
Information system security management is very important for Aceh Government institutions in managing information assets that refer to a standard. This will have a negative impact on the sustainability of information services, especially e-mail services managed by the Aceh Communication, Information, and Encryption Service. So the need for good management governance according to national and international standards to create good management of electronic mail information system services by conducting an internal audit process on its management in terms of physical and environmental security where the electronic mail service information system is managed. This study discusses the "Information System Security Audit on Data Centers Using SNI-ISO 27001 Standards (Case Study: Aceh Government)". The results showed the need for data and documentation of the final evaluation of the maturity level of the audit process to reduce the risk of threats to the information system generated so that problems can be overcome by making efforts to minimize the possible risks that have been caused. The auditing stages have been carried out on the information system in the data center using the SNI-ISO 27001 standard resulting in a level of maturity still at the "repeatable but intuitive" level that still requires further supervision in the management of the security side.